2020
DOI: 10.3390/ma13040999
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modifications of Poly(Ether Ether Ketone) via Polymerization Methods—Current Status and Future Prospects

Abstract: Surface modification of poly(ether ether ketone) (PEEK) aimed at applying it as a bone implant material aroused the unflagging interest of the research community. In view of the development of implantology and the growing demand for new biomaterials, increasing biocompatibility and improving osseointegration are becoming the primary goals of PEEK surface modifications. The main aim of this review is to summarize the use of polymerization methods and various monomers applied for surface modification of PEEK to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 93 publications
0
22
0
Order By: Relevance
“…Although a large amount of literature has reported that osseointegration and soft tissue binding ability of PEEK materials can be enhanced through structural or surface modification. [28][29][30] Further animal and related experiments are still necessary for these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Although a large amount of literature has reported that osseointegration and soft tissue binding ability of PEEK materials can be enhanced through structural or surface modification. [28][29][30] Further animal and related experiments are still necessary for these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Reversible deactivation radical polymerization techniques are currently one of the most influential solution in the preparation of precisely defined polymers with a predetermined structure and specialist purposes 26‐28 . It is compatible for modification of a wide range of substrates, ranging from naturally derived structures 27,29‐31 going to flat surfaces 32‐35 and nanoparticles, 36‐40 receiving functional hybrid nanomaterials. In this consideration, atom transfer radical polymerization approach (ATRP) technique combined with a “core‐first” approach is especially privileged in the preparation of the architecture polymers from polyphenol compound as naturally derived cores 15,41,42 .…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of grafting well-defined polymer brushes from inorganic as well as organic surfaces opens the way to modern hybrid systems considered materials of the future. Recent literature reports indicate the versatility of the surface modification methods [1][2][3][4][5]. Particularly interesting are the techniques of reversible-deactivation radical polymerization (RDRP), allowing the control of the density and length of surface-grafted macromolecules at the same time leading to the formation of complex polymer brush architectures, rising from the initiation site attached to the surface according to the grafting from approach [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of methods have been used for modification of inorganic and organic surfaces with various polymeric brushes, including reversible addition-fragmentation chain transfer polymerization (RAFT) [15][16][17][18][19][20], nitroxide-mediated polymerization (NMP) [21][22][23], as well as atom transfer radical polymerization (ATRP) [4,14,[24][25][26][27][28][29][30][31]. The ATRP technique is distinguished by a wide spectrum of advantages making it a useful tool for the synthesis of new functional materials.…”
Section: Introductionmentioning
confidence: 99%